PERANCANGAN SISTEM INFORMASI PEMETAAN ALUMNI STIKES SYEDZA SAINTIKA BERBASIS WEB GIS - Herman Susilo (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
SYEDZA Saintika School of Health (STIKes) is one of the Private Educational Institutions established in 2008 under the auspices of the West Sumatra Human Resource Development Foundation located at Jl. Prof. Dr. Hamka No. 228 Air Tawar Timur Padang West Sumatra, which is engaged in health education. SYEDA Saintika STIKes have 6 Study Programs namely Midwifery (D3), Nursing (S1), Professional Ners (Profession), Public Health (S1), Medical Laboratory Technology (D4) and Health Information Management (D4). SYEDZA Saintika STIKes carry out graduation twice in one year, namely in the Odd semester around April and Even Semester in November, in 2018 the number of graduates is recorded at 1,787 people, the number will continue to grow as more people are interested in taking health education and trust in this institution. The SYEDZA Saintika STIKes alumni have been scattered throughout the provinces in Indonesia and have even worked abroad in various disciplines, thus an application or a system that is able to record or map the alumni is needed specifically for their work, this data later it can be used as a reference for institutions to determine the relevance of pendidian to alumni work. By utilizing WEB GIS-based Computer Technology can present data on SYEDZA Saintika alumni alumni in the form of maps and facilitate access to information and location of the alumni's whereabouts.